How much do we know about the effectiveness of warm-up intervention on work related musculoskeletal disorders, physical and psychosocial functions: protocol for a systematic review - Nicolas Larinier; Romain Balaguier; Nicolas Vuillerme (BMJ Open)
Introduction Work-related musculoskeletal disorders (WMSDs) are a growing worldwide burden and effective interventions to prevent them are needed. Physical activity at the workplace is now recognised as a relevant component of WMSDs prevention. Along these lines, warm-up interventions are now offered in a large number of companies to manage WMSDs. Although benefits of warm-up have been previously documented in sports context, to the best of our knowledge, the effectiveness of such intervention in workplaces still remains to be established. Within this context, the aim of the present review is to identify from published literature the available evidence regarding the effects of warm-up on WMSDs and physical and psychosocial functions.Methods The following electronic databases will be searched (from inception onwards to June 2020): Cochrane Central Register of Controlled Trials, PubMed (Medline), Web of Science and Physiotherapy Evidence Database. Randomised and non-randomised controlled studies will be included in this review. Participants should be adult employees without specific comorbidities. Interventions should include a warm-up physical intervention in real-workplaces. The primary outcomes will be pain, discomfort or fatigue. The secondary outcomes will be job control or motivation at work. This review will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines and two team members will independently screen all citations, full-text articles and abstract data. A systematic narrative synthesis will be provided with information presented in the text and tables to summarise the characteristics and findings of the included studies.Ethics and dissemination The approval of an ethical committee is not required. All the included studies will comply with the current ethical standards. The results of this review will summarise the effects of warm-up intervention on WMSDs, physical or psychosocial functions. This information could help professionals in decision making related to the use of these interventions to prevent WMSDs. Findings will be disseminated to academic audiences through peer-reviewed publications, as well as to policy-makers.PROSPERO registration number CRD42019137211.